POLITICAL MARKETING DAN MEDIA SOSIAL (Studi Political Marketing Capres RI 2014 Melalui Facebook) - Christiany Juditha (BPSDMP Kominfo Jakarta, 2015)
The background of this research is the phenomenon of wasteful cost of political campaigns in the 2014 presidential election and the distrust towards the candidate of the leaders. This study focuses on the issue of political marketing. The research objective is to get an overview of candidates political marketing (Prabowo and Jokowi) through Facebook. The method used is qualitative content analysis of the 4 categories of political marketing: policy, figures, parties and imaging. The study concluded that Prabowo policies tend to be global while Jokowi sectoral. Prabowo was described as confident, assertive, strong, trustworthy person and experienced one. Jokowi was depicted as a person who always listen, pay attention, love, defend and likes blusukan. Prabowo wanted to build a democratic nation. While Jokowi hoped Indonesia as a sovereign, independent, and cultured state. In image building, Prabowo highlighted the desire of supporters while Jokowi highlighted the working program. Political marketing is an attempt to provide political education by offering product quality according to the needs of society. Presidential candidates need to understand and carefully offer a product for public policy requires a presidential candidate who is able to accomplish state country, not rhetoric. Keywords : Political marketing; social media, presiden candidate; general election; Facebook. ABSTRAKBerlatarbelakangkan fenomena borosnya biaya kampanye politik dalam pilpres 2014 dan masih sangat tingginya ketidakpercayaan masyarakat terhadap calon pemimpin, penelitian ini fokus pada persoalan pemasaran politik (political marketing). Tujuannya untuk mendapatkan gambaran political marketing capres Prabowo dan Jokowi melalui Facebook. Metode yang digunakan adalah analisis isi kualitatif dengan 4 kategori political marketing : kebijakan, figur, partai dan pencitraan. Hasil penelitian menyimpulkan kebijakan Prabowo bersifat global sementara Jokowi per sektoral. Prabowo digambarkan sebagai pribadi yang percaya diri, tegas, kuat, amanah dan berpengalaman. Jokowi tergambar sebagai pribadi yang selalu mendengar, memperhatikan, mencintai, membela serta gemar blusukan. Prabowo ingin membangun demokrasi bangsa, sementara Jokowi berharap Indonesia sebagai negara berdaulat, berdikari dan berkebudayaan. Dalam membangun pencitraannya, Prabowo sangat menonjolkan keinginan para pendukungnya, sedangkan Jokowi lebih menonjolkan program kerja. Political marketing merupakan upaya untuk memberikan pendidikan politik dengan menawarkan produk berkualitas sesuai kebutuhan masyarakat. Capres perlu memahami dan cermat dalam menawarkan produk kebijakan karena kini masyarakat membutuhkan capres yang mampu menyelesaikan persolan negara, bukan hanya sekedar retorika belaka.Kata Kunci : Political marketing; media sosial ;calon presiden; Pemilu; Facebook.